2022
DOI: 10.1039/d2ta07729a
|View full text |Cite
|
Sign up to set email alerts
|

Origin of photovoltaic losses in selenium solar cells with open-circuit voltages approaching 1 V

Abstract: Research on selenium solar cells is regaining momentum due to the exciting prospect of integrating a single-element, wide-bandgap (≈1.95 eV) photoabsorber in tandem with a lower bandgap photovoltaic device. Low...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…Specifically, the devices using fluorine doped tin oxide (FTO) instead of ITO show no S-shaped kink in the J-V curve, which indicates that the carrier transport barrier could be attributed to the ZnMgO/TCO-interface. ZnMgO was first suggested for use in selenium thin-film solar cells by Todorov et al, 27 and later played a key role in achieving the record opencircuit voltage of V oc =0.99 V. 23 However, all ZnMgO-based selenium solar cells reported in literature have been synthesized on FTO-coated glass, whereas the devices fabricated on ITO use TiO 2 instead of ZnMgO as the n-type contact material. 26,33 To investigate the sensitivity towards the choice of TCO, we synthesize ZnMgO, TiO 2 and poly-Se thin-films and examine their relative energy band positions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the devices using fluorine doped tin oxide (FTO) instead of ITO show no S-shaped kink in the J-V curve, which indicates that the carrier transport barrier could be attributed to the ZnMgO/TCO-interface. ZnMgO was first suggested for use in selenium thin-film solar cells by Todorov et al, 27 and later played a key role in achieving the record opencircuit voltage of V oc =0.99 V. 23 However, all ZnMgO-based selenium solar cells reported in literature have been synthesized on FTO-coated glass, whereas the devices fabricated on ITO use TiO 2 instead of ZnMgO as the n-type contact material. 26,33 To investigate the sensitivity towards the choice of TCO, we synthesize ZnMgO, TiO 2 and poly-Se thin-films and examine their relative energy band positions.…”
Section: Resultsmentioning
confidence: 99%
“…This point is consistent with our previous publications on improving the optoelectronic quality of the selenium absorber. 20,23 However, prior to undertaking elaborate efforts in defect-engineering of selenium, it is essential to determine the appropriate substrate materials on which to grow the absorber. The results of this work demonstrate the significant impact of using ITO instead of FTO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser-annealing is a compelling alternative to thermal annealing, as the energy induced upon exposure may be accurately localized in time and space. , This enables excellent control of the crystallization process as well as the crystal growth direction. The latter is particularly important in the case of trigonal selenium, as the optoelectronic material properties are anisotropic . The crystallographic orientation of the grains in the selenium thin-film is therefore expected to affect the PV device performance.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is particularly important in the case of trigonal selenium, as the optoelectronic material properties are anisotropic. 14 The crystallographic orientation of the grains in the selenium thin-film is therefore expected to affect the PV device performance. The crystallization of amorphous selenium under the influence of light was first studied half a century ago, where it was observed that illumination increases the growth rate of crystallites and modifies their external morphology.…”
Section: ■ Introductionmentioning
confidence: 99%